Agriculture Vocational Public High School by Modernizing Indonesian Architecture in Randu Village of Batang Regency - Reviyana Ranti (Jurnal Poster Pirata Syandana, 2023)
In the standards of educational facilities and infrastructure, school buildings are influential in the educational process. The Minister of National Education, through Government Regulation Number 40 of 2008 about Standards for Facilities and Infrastructure for Vocational High Schools, has set criteria for meeting infrastructure standards, including those related to education units, land, buildings, and other equipment. Fulfilling these criteria forms the basis for meeting the minimum standards for potential development facilities, especially for Vocational High Schools. Batang Regency has relatively agricultural potential. Unfortunately, the educational facilities there, formal schools, and informal academies, need to be more robust to support knowledge and skills in agricultural technology. The Central Board of Statistics for Batang Regency also stated that the quality of human resources in Batang Regency could have been more optimal. It has caused many residents to choose to become farmers abroad rather than become farmers in Indonesia. In fact, with its rich natural and agricultural resources, Indonesia can strengthen its agricultural potential and boost the country's economy. Keywords: Vocational High School; Agriculture; Batang Regency.